Sodium content of processed foods in the United Kingdom: analysis of 44,000 foods purchased by 21,000 households. - Ni Mhurchu, C; Capelin, C; Dunford, E; Webster, J; Neal, B; Jebb, SA (2011)
BACKGROUND: In the United Kingdom, sodium reduction targets have been set for a large number of processed food categories. Assessment and monitoring are essential to evaluate progress. OBJECTIVES: Our aim was to determine whether household consumer panel food-purchasing data could be used to assess the sodium content of processed foods. Our further objectives were to estimate the mean sodium content of UK foods by category and undertake analyses weighted by food-purchasing volumes. DESIGN: Data were obtained for 21,108 British households between October 2008 and September 2009. Purchasing data (product description, product weight, annual purchases) and sodium values (mg/100 g) were collated for all food categories known to be major contributors to sodium intake. Unweighted and weighted mean sodium values were calculated. RESULTS: Data were available for 44,372 food products. The largest contributors to sodium purchases were table salt (23%), processed meat (18%), bread and bakery products (13%), dairy products (12%), and sauces and spreads (11%). More than one-third of sodium purchased (37%) was accounted for by 5 food categories: bacon, bread, milk, cheese, and sauces. For some food groups (bread and bakery, cereals and cereal products, processed meat), purchase-weighted means were 18-35% higher than unweighted means, suggesting that market leaders have higher sodium contents than the category mean. CONCLUSION: The targeting of sodium reduction in a small number of food categories and focusing on products sold in the highest volumes could lead to large decreases in sodium available for consumption and therefore to gains in public health.